Myths, the Bible, and Romanticism as ingredients of political narratives in the Finns Party election video. (March 2021) - Martikainen, Jari; Sakki, Inari
Highlights: Election video uses myths, Bible stories, and Romantic visual imagery as discursive devices in the populist communication. Palingenetic myth is used as means of political persuasion. Myths, Bible stories and Romantic imagery appeal to emotions and construct social identities. Art historical styles serve a rhetorical resource to construct intergroup differentiation. Abstract: This research set out to examine how ancient myths, Bible stories, and romantic visual imagery were used as discursive devices in the populist communication of the 2019 Finns Party election video. This study draws from systematic functional multimodal discourse analysis and its concepts of intersemiotic texture, co-contextualization, and re-contextualization to examine how different semiotic resources work together in the video. The multimodal analysis demonstrated the aforementioned resources served as a means of constructing a palingenetic myth, intertwining mythical resources with current social and political circumstances in Finland. Together, the verbal, visual, and sonic modalities as well as the mythical, biblical, and artistic rhetorical devices constructed multimodal political communication that was capable of appealing to emotions, constructing collective identities, and mobilizing people.